1997
DOI: 10.1103/physrevc.55.640
|View full text |Cite
|
Sign up to set email alerts
|

Isospin mixing in37K and spin decomposition of Gamow-Teller strength in37Ca decay

Abstract: We measured 36 Ar(p ជ ,p 0 ) cross sections and analyzing powers for E p between 3.22 and 5.98 MeV, and used these data to deduce spin, parity, and widths of 17 levels in 37 K. Our results, combined with existing information on 37 Ca ␤ ϩ decay, yield information on the distribution of Fermi and Gamow-Teller strength in this decay. A Tϭ1/2 level lying 31 keV below the J ϭ3/2 ϩ , Tϭ3/2 analog of the 37 Ca ground state was found to have J ϭ3/2 ϩ . The relative proton widths of the two levels imply an isospin-mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…The currents are consistent with the solar isotopic abundances for argon, yielding no evidence for beam contaminants that would lead to target contamination. Similar results have been found by other groups [27].…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The currents are consistent with the solar isotopic abundances for argon, yielding no evidence for beam contaminants that would lead to target contamination. Similar results have been found by other groups [27].…”
Section: Methodssupporting
confidence: 93%
“…Additionally, 28 Si(d, t) 27 Si peaks (E x ≈ 4.2-4.5 MeV) were used at 20°and 25°. A quadratic least squares fit was used to calibrate momentum vs. position centroid.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The studies of 36 Ca(p, γ ) 37 K [17] and 40 Ca(p, α) 40 K [18] reactions suggested that a few protonunbound states in 37 K above the proton separation energy had significant probabilities of undergoing γ decay. Actually recalculation of the B(GT) distribution by taking both the delayed proton emission and the γ decay into account reduced a large part of the difference [19,20].…”
mentioning
confidence: 99%
“…[24][25][26] as described in Ref. [27]. In order to disentangle the different contributions to the energy resolution in our excitation functions we took data with two different Ag 2 S targets: one 9.3 times thinner than the other one (as measured by the yields in a given detector).…”
mentioning
confidence: 99%